The Effect of Perceived Usefulness and Perceived Ease of Use on Interest in Using Telemedicine Moderated by the Level of Technological Skills - Nurdianti, Deti; Gunardi, Wani Devida; Fushen, Fushen (Syntax Corporation, 2026)
The use of telemedicine continues to develop as it facilitates access to healthcare services. However, its utilization rate at PT. X remains low, even though the company has provided an internal application as part of the digitalization of clinic services. This study aims to analyze the influence of perceived usefulness and perceived ease of use on the intention to use telemedicine, with technological skill level as a moderating variable. The study employs a descriptive method with a quantitative approach. This quantitative observational research was conducted at PT. X using a cross-sectional design. The study was carried out from June to August 2025 at PT. X. The population consisted of all PT. X employees, totaling 8,000 individuals. The sample size was determined using the Slovin formula, resulting in 99 respondents. The sampling technique used was non-probability sampling with accidental sampling. The sample criteria were determined based on inclusion and exclusion criteria. The independent variables in this study were perceived usefulness and perceived ease of use, the dependent variable was the intention to use telemedicine, and the moderating variable was the level of technological skills. The research instrument employed was a questionnaire using a Likert scale. The data analysis technique used in this study employs the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, which is conducted through outer model and inner model testing with the assistance of SmartPLS 4.1.0.0. The results of the study indicate that: (1) Perceived usefulness has a positive and significant effect on employees’ intention to use telemedicine at PT. X; (2) Perceived ease of use does not affect employees’ intention; (3) Technological skill level does not successfully moderate the relationship between perceived usefulness and intention; (4) Technological skill level negatively moderates the relationship between perceived ease of use and intention; (5) Technological skill level does not have a direct effect on employees’ intention to use telemedicine at PT. X.